An Ultrabroadband Mid‐Infrared Pulsed Optical Switch Employing Solution‐Processed Bismuth Oxyselenide - Tian, Xiangling; Luo, Hongyu; Wei, Rongfei; Zhu, Chunhui; Guo, Qianyi; Yang, Dandan; Wang, Fengqiu; Li, Jianfeng; Qiu, Jianrong (Advanced materials (Weinheim), 2018)
Pulsed lasers operating in the mid‐infrared (3–25 µm) are increasingly becoming the light source of choice for a wide range of industrial and scientific applications such as spectroscopy, biomedical research, sensing, imaging, and communication. Up to now, one of the factors limiting the mid‐infrared pulsed lasers is the lack of optical switch with a capability of pulse generation, especially for those with wideband response. Here, a semiconductor material of bismuth oxyselenide (Bi2O2Se) with a facile processibility, constituting an ultrabroadband saturable absorber for the mid‐infrared (actually from the near‐infrared to mid‐infrared: 0.8–5.0 µm) is exhibited. Significantly, it is found that the optical response is associated with a strong nonlinear character, showing picosecond response time and response amplitude up to ≈330.1% at 5.0 µm. Combined with facile processibility and low cost, these solution‐processed Bi2O2Se materials may offer a scalable and printable mid‐infrared optical switch to open up the long‐sought parameter space which is crucial for the exploitation of compact and high‐performance mid‐infrared pulsed laser sources. An ultrabroadband mid‐infrared saturable absorber based on facilely prepared Bi2O2Se is associated with a strong nonlinear character, revealing picosecond response time from 1.55 to 5.0 µm and modulation response up to ≈330.1% at 5.0 µm. A 2.86 µm Ho3+/Pr3+‐codoped fluoride fiber laser passively Q‐switched by a Bi2O2Se‐based saturable absorber is investigated.